Novel method for the genomic analysis of PKD1 mutation in autosomal dominant polycystic kidney disease - Shang, Shunlai; Wang, Chao; Chen, Lang; Shen, Wanjun; Xie, Yuansheng; Li, Wenge; Li, Qinggang (Frontiers in Cell and Developmental Biology, 2023)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disease. Next-generation sequencing (NGS) technology can sequence tens of thousands of DNA molecules simultaneously,. However, NGS has poor capture efficiency for the six PKD1 pseudogenes and GC-rich regions. Multiplex ligation-dependent probe amplification (MLPA) technology can detect consecutive deletions of exons, but it is less sensitive to single-base mutations. Even with the above methods, no pathogenic genes are detected in some patients. Improving the detection rate of pathogenic genes is an important technical problem hindering the clinical diagnosis of ADPKD. Four pedigrees of ADPKD patients whose mutation sites were not identified by NGS were examined by other methods. First, MLPA was performed. Then, pedigrees in which MLPA did not identify pathogenic genes were subjected to multiplex polymerase chain reaction (MPCR) and targeted region sequencing. Finally, the detected mutation sites were verified by Sanger sequencing. Results show MLPA detected the following PKD1 exonic deletion mutations in three pedigrees: PKD1-18-290 nt, PKD1-up-257 nt, PKD1-up-444 nt, and PKD1-3-141 nt. A new mutation site was identified through targeted region sequencing in one pedigree: PKD1 Chr16-2185540. In summary, We established a set of genetic detection and analytical methods, going from NGS to MLPA to targeted region sequencing and finally to Sanger sequencing. We combined MPCR and targeted region sequencing for the first time in ADPKD diagnosis, which further improved the accuracy of the diagnosis. Moreover, we identified one new missense mutation and four new deletion mutations .